Application of Digital Technologies in the Virtual Learning Environment Moodle in Distance Education: a systematic review (Research, Society and Development, 2022)
Starting from the recurring discussions about the application of digital technologies in virtual learning environments, this study aimed to analyze how the application of digital technologies in the virtual learning environment Moodle has taken place, and how teachers have developed pedagogical practices considering digital universe and the transformations experienced in the educational context. For this, the Systematic Review of Literature - LSR, based on research method proposed by Kitchenham (2004), which is intended to define research questions as well string conducted by databases. From this perspective, the following search string was defined: "digital technologies" AND "virtual environments" OR "AVA" AND "moodle" OR "learning management system" OR "LMS" AND "teacher training" AND "EaD". Therefore, the digital repositories selected for the research were Science Direct (Elsevier), IEEE-Xplore, ACM Digital Library e Academic Search Premier - ASP (EBSCO) from 2016 to 2020 was the time frame for data analysis. Therefore, after the discussions, it became evident that the moodle platform is considered one of the most used and allows a range of interactions, as it is free software, it allows the insertion of collaborative tools, as well as the application of resources in its source code. Capable of assisting the pedagogical practices carried out by teachers, in addition to the customization of existing resources, however, there is still a gap in this training process and this directly reflects on the results in the classroom.